Material point method investigation of thermal effects on combustion evolution in composition B explosive - Weidong CHEN; Peiwen WU; Shengzhuo LU; Shibo WU; Mingwu SUN; Bo SUN (Results in Engineering)
Thermal stimuli play a critical role in ammunition integrity studies, where understanding their effects on the combustion evolution of energetic materials is essential for safety engineering. Although deflagration-to-detonation transition (DDT) tests under thermal stimulation provide pressure field and shockwave propagation data, they cannot directly reveal the mechanisms governing the combustion ignition threshold, the reaction evolution mode, and the initial detonation depth in energetic materials. Therefore, based on the DDT trial data, a Material Point Method (MPM) was applied to investigate the initial temperature effect on the thermal stimulated combustion evolution of the Composition B explosive, as well as to explore the above mechanisms. Numerical results conclude four findings. Firstly, the ignition mechanism during combustion evolution can be analyzed via pressure and pressure-rise rate. Secondly, the mechanism of self-sustaining detonation can be evaluated based on variations in pressure and macroscopic reaction progress. Additionally, higher initial temperatures increase the likelihood of ignition at lower pressures and produce slower reaction waves, which under reduced confinement may inhibit detonation. Nevertheless, initial temperature influences the propagation speed of the initial planar shock wave and the magnitude of the initial detonation pressure rather than the pressure or velocity of the steady detonation.